2023
DOI: 10.1108/ict-03-2022-0017
|View full text |Cite
|
Sign up to set email alerts
|

Occupational stress among Generation-Y employees in the era of COVID-19: cases from universities in India

Abstract: Purpose Several organizations decided to work remotely after the Indian Government proclaimed a state of emergency on March 24, 2020, to prevent the spread of COVID-19. Employees across all industries, particularly the Generation-Y, were stressed as a result of the COVID-19 outbreak. The purpose of this study is to fills that gap by looking at the effects of occupational stress factors (such as coworker support, work–life balance [WLB] and role expectation conflict) on Generation-Y employees in the educational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 86 publications
(128 reference statements)
0
4
0
Order By: Relevance
“…The current study uses descriptive statistics, correlations and SEM for data analysis (Yasir et al , 2023). The correlation between the results of the survey and the hidden variables was investigated using a measurement model (Said et al , 2023). To investigate the linear relationship, we used the covariance approach.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study uses descriptive statistics, correlations and SEM for data analysis (Yasir et al , 2023). The correlation between the results of the survey and the hidden variables was investigated using a measurement model (Said et al , 2023). To investigate the linear relationship, we used the covariance approach.…”
Section: Methodsmentioning
confidence: 99%
“…Employees are motivated to work hard towards organizational goals when supervision is perceived as supportive, aligning with the goals of high-commitment HRM practices (S. C. H. Chan, 2017). With this approach, a supervisor can build confidence in employees regarding their ability to achieve assigned goals (Said et al , 2019).…”
Section: Trustmentioning
confidence: 99%
“…To validate the questionnaire, we employed the content and face validity methods used in previous studies [ 71 ]. The questionnaire was first evaluated by four experts from the Department of User Behavior of E-commerce [ 72 ]. It was then read by 30 volunteers who were recruited from 2 universities in Fujian province, China, who were asked to provide any recommendations to ensure that every item was clear and readable.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, there is strong evidence in the literature that HR practices, such as compensation and training, have a direct influence on employee work engagement (Aboramadan et al, 2020;Ferenhof et al, 2015;Jurek and Besta, 2021;Kashyap et al, 2022). The term compensation refers to characteristics that talk about bounces, rewards, financial incentives and growth in salary (Said et al, 2023;Ybema et al, 2020). Past studies have clearly revealed the positive impact of compensation on employee work engagement (Aboramadan et al, 2020;Jurek and Besta, 2021;Kashyap et al, 2022).…”
Section: Hr Compensation and Trainingmentioning
confidence: 99%